2011
DOI: 10.1128/aem.01174-10
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of the Lactococcus lactis Transcriptome in Cheeses Made from Milk Concentrated by Ultrafiltration Reveals Multiple Strategies of Adaptation to Stresses

Abstract: Lactococcus lactis is used extensively for the production of various cheeses. At every stage of cheese fabrication, L. lactis has to face several stress-generating conditions that result from its own modification of the environment as well as externally imposed conditions. We present here the first in situ global gene expression profile of L. lactis in cheeses made from milk concentrated by ultrafiltration (UF-cheeses), a key economical cheese model. The transcriptomic response of L. lactis was analyzed direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 44 publications
(55 reference statements)
8
61
0
Order By: Relevance
“…casei inhibition of S. aureus internalization probably involves one or more means acting alone or in combination: (i) modulation of bMEC physiology or integrity induced by contact; (ii) direct effect on S. aureus, including coaggregation, as observed for vaginal lactobacilli (47,48), although preliminary experiments indicated that L. casei 667 exhibited poor aggregative abilities (data not shown); (iii) inhibition of S. aureus virulence expression, including major virulence regulators, as previously reported (48)(49)(50)(51); and (iv) competition for attachment sites involved in internalization. In agreement with a competition mechanism, the L. casei internalization rate was also affected by S. aureus.…”
Section: Discussionmentioning
confidence: 79%
“…casei inhibition of S. aureus internalization probably involves one or more means acting alone or in combination: (i) modulation of bMEC physiology or integrity induced by contact; (ii) direct effect on S. aureus, including coaggregation, as observed for vaginal lactobacilli (47,48), although preliminary experiments indicated that L. casei 667 exhibited poor aggregative abilities (data not shown); (iii) inhibition of S. aureus virulence expression, including major virulence regulators, as previously reported (48)(49)(50)(51); and (iv) competition for attachment sites involved in internalization. In agreement with a competition mechanism, the L. casei internalization rate was also affected by S. aureus.…”
Section: Discussionmentioning
confidence: 79%
“…During fermentation in milk, some amino acids are excreted by L. lactis (43)(44)(45), indicating that the amino acid composition of the peptides taken up after the hydrolysis of casein by PrtP is not matching the requirements for biosynthesis. The excretion of excess amino acids was proposed to be coupled to the excretion of a proton (proton symport), which would contribute to the generation of metabolic energy in the form of proton motive force (PMF) (energy-recycling model).…”
Section: Discussionmentioning
confidence: 99%
“…cremoris strains under conditions simulating cheddar cheese manufacture (Taïbi et al, 2011) and for the study of iron acquisition by Arthrobacter arilaitensis in experimental cheeses (Monnet et al, 2012 Experimental cheeses L. lactis subsp. lactis bcaT, codY, serA, cysK, gltD, lacC, gapA, gapB, pdhB, aldB, butA, noxE, murF, dnaK, chiA, pepN, gyrB, pi139, pi302 Experimental cheeses (Cretenet et al, 2011) L. lactis subsp. cremoris bcaT,clpE,dnaG,gapA,glyA,groEL,oppA,pepQ,purD,ldh,holin1,holin2 Experimental cheeses (Taïbi et al, 2011) Lb.…”
Section: Real-time Pcr Methodsmentioning
confidence: 99%
“…The calculated fold-change does not reflect the specific gene expression of each population, but rather an expression taking into account the total amount of 16S rRNA. Cretenet et al (2011) quantified the expression of several genes from L. lactis in model cheeses made from ultrafiltered milk, using gyrB (DNA gyrase subunit B) as reference gene. The histidine decarboxylase gene (hdcA) present in certain Str.…”
Section: Real-time Pcr Methodsmentioning
confidence: 99%
See 1 more Smart Citation